Modèles de simulation et de prévision sur une grande échelle - Cole, Sam (L'Actualité économique, 1975)
Since the publication three years ago of the 'global' models of World Dynamics and The Limits of Growth, there has been revived interest in the possibilities of using large scale computer models for the forecasting of long term futures. Although these particular models received considerable criticism, on technical and ideological grounds, the idea that such models may ultimately be useful for seeking out desirable futures and anticipating the dangers in achieving them remains attractive and a number of new global modelling projects are now underway at various institutions around the world.In general these large models have met with mixed success and, at a time when the use of computer models seems likely to become a more widespread feature of our society, it is instructive to examine the reasons why. In particular, it is important to examine the limitations of models proposed for use in the public policy domain.